CMOS MEMS Design and Fabrication Platform - Tseng, Sheng-Hsiang (Frontiers in Mechanical Engineering, 2022)
This article mainly describes the technology related to the CMOS MEMS process platform provided by the Taiwan Semiconductor Research Institute (TSRI), including the process flow, design verification, back-end dicing, and packaging of the CMOS MEMS integrated sensing single chip. The front-end CMOS processes can be a standard 0.35 µm or 0.18 µm CMOS process, or even a BCD high-voltage process. Some academic designs also utilize this platform for in-house post-CMOS process. Finally, the article also explains in detail the CMOS MEMS design flowchart and implementation method provided by TSRI.